2016
DOI: 10.1177/0897190015611774
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use With the ATP III Guidelines Compared to the 2013 ACC/AHA Guidelines in HIV Primary Care Patients

Abstract: A moderate agreement was found between both guidelines in terms of statin use when applied to an HIV patient population. Based on the 2013 guidelines and taking into account drug interactions with antiretrovirals, 44.2% of the patients were treated with an incorrect statin intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…The higher proportion with an indication for statin therapy by ASCVD relative to FRS guidelines has also been reported among other HIV patient populations [ 19 , 20 ]. Yet, there was high agreement between ASCVD and FRS in our cohort as has been reported in other small clinical HIV-cohorts [ 21 ]. Thus, the choice of tool is much less relevant than implementation of screening in general.…”
Section: Discussionsupporting
confidence: 87%
“…The higher proportion with an indication for statin therapy by ASCVD relative to FRS guidelines has also been reported among other HIV patient populations [ 19 , 20 ]. Yet, there was high agreement between ASCVD and FRS in our cohort as has been reported in other small clinical HIV-cohorts [ 21 ]. Thus, the choice of tool is much less relevant than implementation of screening in general.…”
Section: Discussionsupporting
confidence: 87%
“…These prescribing outcomes in team‐based care are much higher than previously described. Three studies observed a rate of 49% to 56% of HIV‐infected patients prescribed statin therapy when indicated and 56% prescribed appropriate statin intensity . Frieberg and colleagues reported that 36% of PLWH with CHD or CHD equivalents did not receive statin therapy; this differed from the current study in which all PLWH with a history of ASCVD or T2DM received statin therapy .…”
Section: Discussioncontrasting
confidence: 72%
“…The difference in statin prescribing between HIV‐infected and uninfected patients has been reported to be as high as 22%, with gross underutilization observed in PLWH with known coronary heart disease (CHD) or risk equivalents . When statin prescribing was assessed in PLWH, less than half of patients in whom a statin was indicated were prescribed these medications (based on the 2013 American College of Cardiology/American Heart Association [ACC/AHA] treatment guidelines) . Given the increase in CVD risk in PLWH, this paper presents the outcomes of statin utilization in PLWH who received team‐based care compared with those who received standard care.…”
Section: Introductionmentioning
confidence: 99%
“…Our direct comparison of ASCVD to FRS in categorizing patient as elevated CVD risk was important to perform as neither risk prediction rule was developed for HIV-infected patients in SSA. In our cohort, ASCVD classified more patients as elevated CVD risk than FRS as has been observed when these two prediction equations are compared among geographically diverse general populations beyond the US general population [ 29 32 ] and some HIV-specific patient population studies [ 12 ] but not all [ 11 , 13 ]. It is possible that the difference in categorizing patients at elevated risk by ASCVD versus FRS in out cohort may reflect the findings that the ASCVD may “over-estimate” risk, even in the general population.…”
Section: Discussionmentioning
confidence: 89%
“…In some HIV-cohorts, ASCVD underestimated CVD risk as compared to actual occurrence of CVD end-points [ 10 , 11 ] or presence of high risk morphology plaque [ 12 ]. Other studies have demonstrated good [ 13 ] versus poor [ 14 ] agreement with the well-established Framingham Risk Score (FRS). The FRS has been reported to accurately predict CVD risk [ 10 , 15 ], underestimate CVD risk [ 12 , 14 ] or overestimate risk [ 15 ].…”
Section: Introductionmentioning
confidence: 99%